Connections between knowledge of mathematics teaching and knowledge of features of learning mathematics: the case of a high-school teacher - Diana Zakaryan; Soledad Estrella; Gonzalo Espinoza-Vásquez; Sergio Morales; Raimundo Olfos; Eric Flores-Medrano; José Carrillo (Enseñanza de las Ciencias, 2018)
A teacher’s knowledge is considered a significant factor contributing to their classroom performance and the promotion of mathematics learning in their students. This paper examines the knowledge deployed by a secondary teacher when working on the topic of similarity of triangles, focusing on the connections between subdomains within Pedagogical Content Knowledge in the model Mathematics Teachers’ Specialized Knowledge. Specifically, drawing on data from lesson observations and interviews with the teacher, it considers connections between the subdomains knowledge of mathematics teaching and knowledge of the features of learning mathematics. The results underline the relationship between research and practice, in that they bring to the fore specific connections between subdomains and their related categories and illustrate how these contribute to classroom decisions.